If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -1(7x + -6) = 14 Reorder the terms: 11x + -1(-6 + 7x) = 14 11x + (-6 * -1 + 7x * -1) = 14 11x + (6 + -7x) = 14 Reorder the terms: 6 + 11x + -7x = 14 Combine like terms: 11x + -7x = 4x 6 + 4x = 14 Solving 6 + 4x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4x = 14 + -6 Combine like terms: 6 + -6 = 0 0 + 4x = 14 + -6 4x = 14 + -6 Combine like terms: 14 + -6 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| 6a+5=3a+26 | | 5(z+3)=95 | | .05(x)=41475-x | | 9+3x=x+25 | | -4y-9=3y+1a | | 8x+11=-21 | | 4x+5=-6+2x+25 | | y/9=72 | | m=19-5(x-n)forn | | 4(5z+1)-6=118 | | -(4y-8)+11=0 | | 0=12(t^2-3t-4) | | 2(5+x)=42 | | -9(x-2)-25=7 | | 2x^2+4x-48= | | x+17=-48 | | (X^3)-(2x^2)-8x=0 | | -9=-c | | 5x(x-2)=6+3x | | 350X+250Y=0 | | -9x^4+36x^2-16=0 | | 10*x=1.3085 | | 4x^3+28x^2+48x= | | 3(3x+1)=2x-4(x+5)+1 | | 30=5v | | 4.7*y=44.18 | | W=2LH+2LW+2HW | | l=21m | | -8(t-7)(2t+1)=0 | | 4xsquare+4x+1=3x+16 | | 5x+7+3x=18+2x+7 | | 3+2x=55 |